Study of the relationship between the generation of solid urban waste and the Gross Domestic Product (GDP) per capita in Brazil (Research, Society and Development, 2021)
The reduction of solid waste generation in Brazil has been addressed for decades, in 2010 with the launch of the National Solid Waste Policy (PSWP), we saw more solid guidelines to promote this reduction. Regarding the process of generating solid urban waste (MSW), several aspects are related, among which, the economic aspects. Given this scenario, this research sought to assess the relationship between the generation of MSW per capita in Brazil and its Gross Domestic Product (GDP) per capita over the first two decades of the 21st century. The data from the reports of the Brazilian Association of Public Cleaning Companies and Special Waste (ABRELPE) and GDP data released by the federal government were used in the analyzes. At the end, it was identified that the indicators are not correlational when from the general point of view of the country, but that it brings a different behavior in some of its regions, which were influenced by economic factors resulting in a different behavior from the national result.